THE THE INFLUENCE OF HALAL AWARENESS, SELLER REPUTATION AND PRODUCT PROMOTION ON THE INTEREST IN BUYING FOOD THROUGH THE SHOPEE APPLICATION - Ulfa, Dita Camelia; Agung Abdullah (UIN Raden Mas Said Surakarta, 2023)
Abstract This study aims to analyze the influence of halal awareness, seller reputation and product promotion both partially and simultaneously on the interest in buying food through the Shopee application, especially for Shopeefood feature service users in the Surakarta City area. As for the type of research method, it is quantitative based on primary data sources and secondary data. Primary data sources are obtained through the dissemination of questionnaires with gform media while secondary data is through books, journals, web pages, etc. The number of samples taken was 120 respondents with nonprobability sampling techniques. The method is carried out by survey. Data analysis techniques to answer hypotheses using multiple linear regression analysis, simultaneous test (F), determination test, and partial test (t) with a significant level of 5% (α = 0.05) processed with the help of SPSS 25 software. Based on the partial test, halal awareness did not have a positive and insignificant effect on buying interest. Simultaneously testing halal awareness, seller reputation and product promotion simultaneously have a positive and significant effect on buying interest. Keywords: halal, reputation, promotion, buying interest.